(3OjhGf CHj JeGes - (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s
(3ChdgG (B:s
(3djS HgG GdebOeI cGdfSNI GdSGHbI, hJHOC HGdTYQ eHGTQI(B: (3jG ehVY GdTQfjI GdhLfGA heUGQY GdEOdGL hGdGSQGA s
(3BNQgG (B:s
(3ef bUjOI jGFjI(B: (3hCfj LOjQ Cf CNGa hCJbj hEf cfJ de CTQc HPj GdYQT KGfjG s
(3fSNI KGfjIs
(3HChdgG JQLeI dCHj JeGes
(3hbO PgHJ GdCfUGa GdSadi ef GdUaMGJ (B251(3, (B252(3, (B265(3, (B267 (3HQhGjI GdUhdj hgj eQJHI CjVkG HGdehVhYGJs
(3hQO CjVkG JMJ Qbe (B475(3, (B667(3, (B873(3, (B917(3, (B2202(3, (B3247 s
267 (3HQhGjI GdUhdj hgj eQJHI CjVkG HGdehVhYGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs